Innowacyjność izb gospodarczych na tle modernizacyjnej funkcji prawa - Dąbrowski, Karol (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
On the basis of extensive sources, the author discusses the meeting point of three phenomena: innovativeness, economic self-governing bodies and the modernizing function of the law. Initially, he analyzes the meaning of the words ‘innovation’ and ‘modernization’. The issue of innovation and innovativeness is described with reference to Joseph Schumpeter. New notions are indicated, that have emerged in academic language: innovative competence, innovative potential, innovative environment, etc. The innovative activity of modern chambers of commerce in Poland is criticized. An attempt is made to draft an ideal model of an innovation incubator. The author identifies the sources of poor development of business environment institutions, as chambers of commerce are defined, as lying in their legal organization, which is faulty in his opinion. As he emphasizes the idea of self-government (differentiating between ‘self-government’ and a ‘self-governing community’) he raises the issue of whether it is feasible to vest the tasks of the central administration in economic self-governing bodies.
The innovativeness of the chambers of commerce against the background of a modernizing function of law